2018
DOI: 10.3390/agronomy8020020
|View full text |Cite
|
Sign up to set email alerts
|

The ALMT Gene Family Performs Multiple Functions in Plants

Abstract: Abstract:The aluminium activated malate transporter (ALMT) gene family is named after the first member of the family identified in wheat (Triticum aestivum L.). The product of this gene controls resistance to aluminium (Al) toxicity. ALMT genes encode transmembrane proteins that function as anion channels and perform multiple functions involving the transport of organic anions (e.g., carboxylates) and inorganic anions in cells. They share a PF11744 domain and are classified in the Fusaric acid resistance prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 79 publications
(207 reference statements)
0
8
0
Order By: Relevance
“…The aluminum-activated malate transporter (ALMT) gene encodes anion transporter/channel and it can transport organic and inorganic anions through the tonoplast and plasma membrane in cells [15,17]. Genes encoding malate transporters have been found in many plant species, such as Arabidopsis (AtALMT1), rape (BnALMT1, BnALMT2), rye (ScALMT1), and soybean (GmALMT1) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aluminum-activated malate transporter (ALMT) gene encodes anion transporter/channel and it can transport organic and inorganic anions through the tonoplast and plasma membrane in cells [15,17]. Genes encoding malate transporters have been found in many plant species, such as Arabidopsis (AtALMT1), rape (BnALMT1, BnALMT2), rye (ScALMT1), and soybean (GmALMT1) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the rubber tree is an Al tolerant plant, its Al tolerant mechanism has not been studied. It was reported that ALMTs played vital roles in Al detoxification of many plants [15,17]. Therefore, identification of ALMTs from rubber tree genome will be helpful for the comprehensive understanding of the Al tolerant mechanism and for the development of Al-resistant cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Two transporter gene families, ALMT (Aluminium Activated Malate Transporter) and MATE, have been identified in plants as responsible for the exudation of organic acids, hence conferring Al tolerance (Magalhaes et al, 2007;Sasaki et al, 2004). The ALMT family comprises of functionally diverse but structurally similar type of ion channels; they are found ubiquitously in all plant species, expressed throughout different tissues and located in either plasma membrane or tonoplast (Liu & Zhou, 2018). The ALMT family is a multigene family, that consists of fourteen members in Arabidopsis (Sharma, Dreyer, et al, 2016) and nine members in rice (Heng et al, 2018).…”
Section: Role Of Ros In Al Exclusionmentioning
confidence: 99%
“…Its role in regards to aluminum is unknown, though it is responsive to cold and stress-related hormones (Kidokoro et al, 2017), and CAMTA2 is a positive regulator of ALMT1 (Tokizawa et al, 2015). ALMTs are anion channels involved in a wide variety of processes, and although ALMT1 is known to be expressed in roots in response to aluminum (Hoekenga et al, 2006), most ALMT are not thought to be involved in aluminum tolerance (Liu & Zhou, 2018). Recent characterization of ALMT10, upregulated in SpAl in a pattern similar to metallothionein, proposes involvement in homeostasis of Clefflux and NO3assimilation, induced by water deficit (Racero & J, 2020).…”
Section: Characterization Of Aluminum Response In a Saccharum Stem Tissuementioning
confidence: 99%